The European Multiculturality: Lifespace of I. Turgénev - Fernández Bueno, Aída (Revista de Filología Románica, 2012)
Looking West, as a plural linguistic and cultural space was a constant in the Russian literature. For Russian writers of the nineteenth century the West was a place of reference and without doubts Turgénev, the Russian classic who was the most pro-European and cosmopolitan, he who lived the longest time outside his country of birth. His physical exile, sometimes forced, opens a cultural, linguistic and psychological gap from his country. There was no total exile, he never broke ties with Russia, but it was no longer possible for him to live there. He was far away, installed in a multicultural and multilingual Europe: in English, German, French or Spanish. Europe becomes his home country, especially during the last 20 years. A large space with possibilities for him to move, create and live in freedom.
Keywords: multilingualism; multiculturality; cosmopolitism; Ivan Turgénev.